Sequential and synchronous skin pattern formation - Cruywagen, G; Maini, P; Murray, J (Plenum Press, 1993)
Mathematical modelling has become a widely accepted method for examining how and why vertebrate skin structures are laid down in an orderly and organized fashion. Although various theoretical models have been proposed for examining the morphogenetic processes responsible for the large variety of patterns observed on animal skin, these processes are still not well understood. By examining a mechanochemical tissue interaction model based on recent experimental evidence we therefore hope to contribute towards the understanding of skin morphogenesis.